2021
DOI: 10.3390/foods10081865
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Spectroscopy (NIRS) as a Tool for Classification of Pre-Sliced Iberian Salchichón, Modified Atmosphere Packaged (MAP) According to the Official Commercial Categories of Raw Meat

Abstract: This study evaluates near-infrared spectroscopy (NIRS) feasibility in combination with various pre-treatments and chemometric approaches for pre-sliced Iberian salchichón under modified atmosphere (MAP) classification according to the official commercial category (defined by the combination of genotype and feeding regime) of the raw material used for its manufacturing (Black and Red purebred Iberian and Iberian × Duroc crossed (50%) pigs, respectively, reared outdoors in a Montanera system and White Iberian × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
4
0
2
Order By: Relevance
“…Se adquirió un espectro (que fue una media de 50 scans) en el rango de 1000 nm a 1800 nm (resolución espectral de 1 nm) por muestra mediante contacto directo de la sonda de fibra óptica ASD con la muestra (Figura 1) (pieza entera curada con tripa, producto loncheado o producto loncheado y envasado al vacío con un plástico de bajo gramaje). Dicho rango es donde se encuentra la información más útil (mayor relación señal/ruido), tal y como señalan otros estudios en productos cárnicos similares realizados con el mismo espectrofotómetro (Ortiz et al, 2021a;Tejerina et al, 2021a) o con otro equipo como el MicroNIRTM 1700 (Cáceres-Nevado et al, 2021). Para el caso de la pieza entera, el espectro fue tomado haciendo un barrido por toda la superficie del lomito (limpia y sin restos de moho de la curación), mientras que en el caso de la muestra loncheada sin y con envase, el espectro se tomó haciendo zigzag sobre la superficie de la muestra.…”
Section: Categoría Comercialunclassified
See 1 more Smart Citation
“…Se adquirió un espectro (que fue una media de 50 scans) en el rango de 1000 nm a 1800 nm (resolución espectral de 1 nm) por muestra mediante contacto directo de la sonda de fibra óptica ASD con la muestra (Figura 1) (pieza entera curada con tripa, producto loncheado o producto loncheado y envasado al vacío con un plástico de bajo gramaje). Dicho rango es donde se encuentra la información más útil (mayor relación señal/ruido), tal y como señalan otros estudios en productos cárnicos similares realizados con el mismo espectrofotómetro (Ortiz et al, 2021a;Tejerina et al, 2021a) o con otro equipo como el MicroNIRTM 1700 (Cáceres-Nevado et al, 2021). Para el caso de la pieza entera, el espectro fue tomado haciendo un barrido por toda la superficie del lomito (limpia y sin restos de moho de la curación), mientras que en el caso de la muestra loncheada sin y con envase, el espectro se tomó haciendo zigzag sobre la superficie de la muestra.…”
Section: Categoría Comercialunclassified
“…Además, se observaron diferencias en la intensidad de reflectancia entre los espectros medios de las distintas categorías comerciales principalmente a estas longitudes de onda. Los espectros obtenidos en este estudio a partir del lomito ibérico fueron similares, en forma y valores de reflectancia, a los obteni-dos en lomo ibérico curado en formato loncheado y envasado (en atmósfera modificada con una proporción de gases de 70 % N 2 y 30 % CO 2 (Ortiz et al, 2021a). En cuanto a los espectros medios por categorías tomados en la pieza entera con tripa, se observó un ligero cambio de tendencia entre los espectros medios de las categorías Verde y Roja en torno a los 1100 nm, donde llegan a cruzarse.…”
Section: Información Espectralunclassified
“…The main advantage of NIR spectroscopy is that it allows a multitude of analytical parameters to be determined in a few minutes, facilitating a more exhaustive control of a large number of individuals or pieces (Prieto, Pawludzyk, Dugan& Aalhus, 2017; Zamora-Rojas, Garrido-Varo, De Pedro-Sanz, Guerrero-Ginel & Pérez-Marín, 2011). In the Iberian sector several research studies have been carried out using quantitative models which have shown a high potential for predicting the fatty acid and stable carbon isotope pro le in subcutaneous fat of the carcass and/or live animal ( The use of NIR spectroscopy in cured products has allowed the prediction of the main quality characteristics in a fast and nondestructive manner (Ortiz, León, Contador & Tejerina, 2021). However, studies of dry-cured ham are rather scarce and include the prediction of texture and color (García, Andrada, Muñoz & Bote, 2005), the sensory characteristics (Hernández-Ramos et al, 2020) or salt content, and the fatty acid oxidation and tocopherol content in sliced and packaged ham (Tejerina et al, 2018) while the investigation of the feasibility of fatty acid pro le prediction has been addressed by only a few studies (Fernández-Cabanás et al, 2011;Tejerina et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several advantages such as the ease of use, a competitive price, the possibility of providing qualitative and quantitative information with a single and non-destructive analysis, as well as its reproducibility and repeatability have induced the implementation of NIRS in the agri-food industry [ 12 ]. This technology has demonstrated great versatility by analysing different type of samples, including Iberian pig products, although these have usually been food samples or carcasses [ 13 , 14 , 15 ], all characterised by a postmortem collection. Other samples such as faeces have received limited attention.…”
Section: Introductionmentioning
confidence: 99%